2018
DOI: 10.1186/s12864-017-4249-6
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing of the monomorphic pathogen Mycobacterium bovis reveals local differentiation of cattle clinical isolates

Abstract: BackgroundBovine tuberculosis (bTB) poses serious risks to animal welfare and economy, as well as to public health as a zoonosis. Its etiological agent, Mycobacterium bovis, belongs to the Mycobacterium tuberculosis complex (MTBC), a group of genetically monomorphic organisms featured by a remarkably high overall nucleotide identity (99.9%). Indeed, this characteristic is of major concern for correct typing and determination of strain-specific traits based on sequence diversity. Due to its historical economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 63 publications
3
33
1
1
Order By: Relevance
“…These studies have been proving that, besides the high nucleotidic similarity between M. bovis strains, several SNPs can be found that help to differentiate clinical isolates. The analysis of 186 whole‐genome sequences of MTC strains isolated worldwide revealed a highly clustered population in agreement with clustering based on clonal complexes (Lasserre et al, 2018). However, another study that analysed 823 genomes of M. bovis strains from different countries and hosts suggested the existence of three lineages (Lb1, Lb2 and Lb3) that do not fully represent the clonal complexes and are mainly clustered based on geographic location (Zimpel et al, 2019).…”
Section: Drivers Of Animal Tb Heterogeneitysupporting
confidence: 62%
“…These studies have been proving that, besides the high nucleotidic similarity between M. bovis strains, several SNPs can be found that help to differentiate clinical isolates. The analysis of 186 whole‐genome sequences of MTC strains isolated worldwide revealed a highly clustered population in agreement with clustering based on clonal complexes (Lasserre et al, 2018). However, another study that analysed 823 genomes of M. bovis strains from different countries and hosts suggested the existence of three lineages (Lb1, Lb2 and Lb3) that do not fully represent the clonal complexes and are mainly clustered based on geographic location (Zimpel et al, 2019).…”
Section: Drivers Of Animal Tb Heterogeneitysupporting
confidence: 62%
“…In our previous study, we have also shown that few M. bovis genomes do not carry any CC genetic marker (Zimpel et al 2017a), a phenomenon that was recently observed in M. bovis isolates from one cattle herd in the USA and from slaughterhouse cattle in Eritrea (Ghebremariam et al 2018; Orloski et al 2018). These findings suggest that Clonal Complexes are unlikely to represent the whole diversity of M. bovis strains, warranting further evaluation of M. bovis molecular lineages (Zimpel et al 2017a; Lasserre et al 2018).…”
Section: Introductionmentioning
confidence: 96%
“…Since the whole-genome sequence of the first M. bovis strain became available in 2003 (Garnier et al, 2003), increasing efforts have been made to sequence additional strains and use whole-genome information to tackle bovine and/or wildlife TB transmission within specific outbreaks or countries (Bruning-Fann et al, 2017; Sandoval-Azuara et al, 2017; Ghebremariam et al, 2018; Kohl et al, 2018; Lasserre et al, 2018; Orloski et al, 2018a; Price-Carter et al, 2018; Razo et al, 2018). However, no studies to date have comprehensively analyzed M. bovis genomes at a global scale.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations